Examining The Narration Of Prophetic Biography In Negeri Sembilan's Primary School Textbook: A Retracement Study - Abdul Rasydan Bin Mohamad Rusli
Prophetic Biography (sīrah) is one of the core subject learned by the children in Negeri Sembilan’s KAFA class. The syllabus must be analysed to ensure the authenticity of facts mentioned, especially which related to the prophet sayings and deeds. Any weak or fabricated facts in the syllabus might contribute to the misunderstanding in the religion. This study aims to discuss the authenticity of facts related to ḥadīths used in the Prophet Background (al-Sīrah al-Nabawiyyah) subject for KAFA in Negeri Sembilan. Besides, this study also will analyze in-depth the reason for the status of ḥadīths in the subject. The discussion will be carried by the method of referring to its original text in the Arabic language. This study will be conducted as a qualitative method in the form of document analysis. From a total of 55 ḥadīths analysed, 29 ḥadīth are authentic, 16 ḥadīths are light weak, 7 ḥadīths are very weak and 3 ḥadīths are fabricated. The researcher hopes the outcome of the research may benefit all in the understanding of the Prophet's background and delivering it to Muslim students in KAFA class of Negeri Sembilan.